Computer-assisted versus paper-and-pencil self-report delinquency surveys: results of an experimental study - Baier, Dirk (European journal of criminology, 2018)
Self-report delinquency studies among adolescents are frequently conducted as paper-and-pencil studies. With the introduction of computers in schools, a new infrastructure for interviewing students is available. Until now only a few criminological studies deal with the question of whether paper-and-pencil and computer-assisted surveys lead to the same results. This question is analysed using a paper-and-pencil sample of 2033 adolescents and a netbook sample of 610 adolescents. In contrast to other experiments, not only are prevalence rates of delinquent behaviour compared but also prevalence rates of factors influencing delinquent behaviour, correlations between these factors and the behaviour, missing values and evaluations of the survey by the adolescents. Among others, the analyses differentiate between gender and educational groups. All in all, largely no differences were found between the two methods regarding all these topics. The netbook survey obtained the same results as the paper-and-pencil survey.